Developing the Business Resilience - Technopreneur and Digital Transformation Model - Tuegeh, Octavia Diana Monica; Nagy, Adrian Szilárd; Paat, Franda Benedicta; Tumiwa , Johan Reineer; Kawet, Frilly (Sam Ratulangi University, 2025)
Abstract: This research aims to develop a business resilience model on MSMEs during COVID-19 theoretically and empirically. This research uses the TCM method for literature review analysis and SEM for model testing. The object population of this research is MSMEs in a rural area in Indonesia. The sample of this research is 301 MSME owners who are still surviving during COVID-19. The results reveal no significant direct influence of government support assistance on business resilience. However, government support assistance, knowledge management, and innovation through technopreneur have a significant impact on digital transformation, and then digital transformation on business resilience. The research made new theoretical and empirical contributions of MSMEs to utilize government support in business resilience models and knowledge management and innovation concerning entrepreneurship. Keywords: Business resilience; COVID-19; digital transformation; government assistance; innovation; knowledge management; MSMEs; technopreneur.